Representation of Fat Women in Wolipop.detik.com and Liputan6.com: A Sara Mill's Analysis Perspective - Rissa Amanda (MediaTor (Jurnal Komunikasi), 2021)
Having an ideal body is a common opinion and stereotype of women's society. They are competing to achieve it all because it is also supported by the depiction of the massive mass media with advertisements that place beautiful and slim women as actors. However, on the other hand, not all women have an ideal body shape like fat women who always get unfair behavior from the dominant society. They become a subculture group that must fight against negative stigma to get justice. It is rare for women to be portrayed positively by the mass media. Using Sara Mills' critical discourse analysis, the writer wants to see how the representation of  fat women at Wolipop.detik.com and Liputan6.com online media through three articles selected from each. This study uses a qualitative descriptive approach. The results show that these two media put writer-reader positions in place that see obese women as a subculture group struggling in the dominant society. However, many are brave enough to speak up nowadays, especially on social media. Wolipop.detik.com places more obese women as subjects, while for Liputan6.com women are told more as objects. These two media are still lack of Indonesian fat women positive stories, meaning that they still adhere to the dominant discourse and values.